2017
DOI: 10.1002/app.45677
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(acrylonitrile‐co‐divinylbenzene‐co‐vinylbenzyl chloride)‐derived hypercrosslinked polymer microspheres and a preliminary evaluation of their potential for the solid‐phase capture of pharmaceuticals

Abstract: Poly[acrylonitrile (AN)‐co‐divinylbenzene (DVB)‐co‐vinylbenzyl chloride (VBC)] terpolymers were synthesized by precipitation polymerization in the form of porous polymer microspheres. The poly(AN‐co‐DVB‐co‐VBC) polymers were then hypercrosslinked, via a Friedel‐Crafts reaction with FeCl3 in nitrobenzene, to provide a significant uplift in the specific surface areas of the polymers. FTIR spectra of the hypercrosslinked poly(AN‐co‐DVB‐co‐VBC)s showed that the chloromethyl groups derived from VBC were consumed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…The absorption band at ∼1,270 cm −1 , which was assigned to the chloromethyl groups, was presented in poly(AN-co-DVB-80-co-VBC) FT-IR spectrum ( Figure 1a); however, this band almost disappeared in the HXL poly(AN-co-DVB-80-co-VBC) spectrum (Figure 1b) following hypercrosslinking, which was the result of the consumption of chloromethyl groups. This confirmed that the hypercrosslinking reaction that involved nucleophilic substitution in the Friedel-Crafts alkylation reaction was successfully carried out (29). Figure 1c shows the FT-IR spectrum of hypercrosslinked poly(AN-co-DVB-80-co-VBC) that was chemically modified with ethylenediamine (EDA).…”
Section: Adsorption Kinetic Studysupporting
confidence: 58%
“…The absorption band at ∼1,270 cm −1 , which was assigned to the chloromethyl groups, was presented in poly(AN-co-DVB-80-co-VBC) FT-IR spectrum ( Figure 1a); however, this band almost disappeared in the HXL poly(AN-co-DVB-80-co-VBC) spectrum (Figure 1b) following hypercrosslinking, which was the result of the consumption of chloromethyl groups. This confirmed that the hypercrosslinking reaction that involved nucleophilic substitution in the Friedel-Crafts alkylation reaction was successfully carried out (29). Figure 1c shows the FT-IR spectrum of hypercrosslinked poly(AN-co-DVB-80-co-VBC) that was chemically modified with ethylenediamine (EDA).…”
Section: Adsorption Kinetic Studysupporting
confidence: 58%
“…This characterization successfully confirmed the size of the particles as reported in the DLS study. The NP diameters and particle size distributions were calculated using Image J software by National Institutes of Health (version 1.52a) from the FESEM image analysis of 30 individual particles [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previously, ion exchange method can be done by using a selected base-sorbent such as silica, carbon and polymer (Subri et al, 2017). However, silica and carbon base-sorbent have showed weaknesses in the systems due to lacking in term of permeability, thermodynamically and mechanical stability (Larous et al, 2018;Fontanal et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Though, different precursors gave different value of SSA through hyper-crosslinking reaction. Subri et al (2017) found that hyper-crosslinking process of precursor particles from acrylonitrile (AN), divinylbenzene (DVB) and vinyl benzyl chloride (VBC) could achieved SSA up to 1078 m 2 g -1 with 4.0 nm of maximum pore size. Fontanal and his co-workers (2015) also managed to obtained SSA up to 1125 m 2 g -1 by hyper-crosslinking precursors particles from methacrylic acid (MMA), DVB and VBC.…”
Section: Introductionmentioning
confidence: 99%